1999
DOI: 10.1080/00288330.1999.9516856
|View full text |Cite
|
Sign up to set email alerts
|

Spawning, settlement, and growth of the New Zealand veneridRuditapes largillierti(Philippi 1849) in culture

Abstract: Spawning, larval rearing, and growout of Ruditapes largillierti (Philippi 1849) were investigated in a series of trials conducted at the University of Tasmania (UTAS), Launceston and Georges Bay, St Helens, Tasmania, Australia. Intramuscular injection of serotonin (3 × 10 -7 to 1.5 × 10 -6 moles) failed to induce spawning in female Ruditapes largillierti, although some males did spawn. Fecundity of R. largillierti induced to spawn by thermal stimulus ranged from 0.5 to 0.9 × 10 6 eggs female -1 . Fertilised eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…Opposite to what was previously reported by Kent et al (1999), the fertilization method used here was very effective as high survival of larvae was observed in treatments where appropriate environmental…”
Section: Discussioncontrasting
confidence: 38%
“…Opposite to what was previously reported by Kent et al (1999), the fertilization method used here was very effective as high survival of larvae was observed in treatments where appropriate environmental…”
Section: Discussioncontrasting
confidence: 38%
“…Both the low temperature and the epinephrine applied during the first 48 h of settlement promoted greater final accumulated survival in the two scallops. Higher percentages of settlement, metamorphosis, and/or survival have been obtained by lowering the temperature for species including Argopecten purpuratus (Uribe et al 1993), C. gigantea (Bourne et al 1989) and Pinctada imbricata (Röding, 1798) (O'Connor & Lawler 2004) and with exposure to epinephrine in A. purpuratus (Abarca & Castilla 1997; Martínez et al 1999), Chlamys varia (Mesías‐Gansbiller et al 2008), Crassostrea gigas (Lamarck, 1819) (Robert & Gérard 1999), Mytilus galloprovincialis (Lamarck, 1819), Venerupis pullastra (Montagu, 1803), Ostrea edulis (Lamarck, 1819) (García‐Lavandeira, Silva, Abad, Pazos, Sánchez & Pérez‐Parallé 2005) and Ruditapes largillierti (Philippi, 1849) (Kent, Maguire, Duthie & Pugh 1999). Nevertheless, it has also been reported that these stimuli had no effects on P. yessoensis (Kingzett, Bourne & Leask 1990), Ruditapes philippinarum (Adams & Reeve, 1850) (García‐Lavandeira et al 2005) and Pinctada margaritifera (Linné, 1758) (Doroudi & Southgate 2002).…”
Section: Discussionmentioning
confidence: 99%